(untitled) - Jurenka, Nancy Allen (Westport, 2005)
Teaching phonemic awareness can be boring and repetitive in the hands of a teacher who wishes to just use a workbook approach. This book packs loads of fun into 75 lesson plans, providing educators with myriad creative strategies for integrating word study with children's picture books. The lessons build skills in phonemic awareness, morphemic analysis, letter identification, sight word identification, rhyming, through singing, dancing, games, art activities, cooking, and interesting experiences, and humorous picture books. The early childhood teacher who is committed to making literacy development meaningful, and as much fun as possible, will enjoy the wealth of valuable material here.
Nhận thức Anh ngữ
Keywords: Tiếng Anh,English language; Ngữ âm,Dạy và học,Study and teaching,Phonemics